The conservatives in crisis : the Tories after 1997 - Garnett, Mark, 1963-; Lynch, Philip, 1967- (Manchester University Press, 2003)
"The Conservatives in crisis provides a timely and important analysis of the Conservative Party's spell in opposition following the 1997 general election. It includes chapters by leading academic experts on the party and commentaries by three senior Conservative politicians: Lord Parkinson, Andrew Lansley MP and Ian Taylor MP. Having been the dominant force in British politics in the twentieth century, the Conservative Party suffered its heaviest general election defeats in 1997 and 2001. This book explores the party's current crisis and assesses the Conservatives' failure to mount a political recovery under the leadership of William Hague. The Conservatives in crisis includes a detailed examination of the reform of the Conservative Party organisation, changes in ideology and policy, the party's electoral fortunes, and Hague's record as party leader. It also offers an innovative historical perspective on previous Conservative recoveries and a comparison with the revival of the US Republican Party. In the conclusion the editors assess the failures of the Hague period and examine the party's performance under Iain Duncan Smith. The Conservatives in crisis will be essential reading for students of contemporary British politics"--Publisher's description